"REBOOT" OF HUMAN CONSCIOUSNESS IN XXI CENTURY: CHALLENGES OF GLOBALIZATION - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article provides a philosophical analysis of the impact of the natural sciences researches results upon the change of human consciousness in the twentieth century.